Moderate Boron Concentration Beneficial for Flue-Cured Tobacco (Nicotiana tabacum L.) Seedlings Growth and Development - Mengxia Li; Haowei Sun; Jianfeng Sun; Jialiang Li; Xiaowei Zhang; Ke Zhang; Tao Wang; Xinwei Ji; Xiaopeng Deng; Chenggang He; Yongzhong Li; Congming Zou (Agriculture, 2022)
Boron (B) deficiency is a common phenomenon in most tobacco-planting areas in Yunnan, China. In 2020 and 2022, hydroponic experiments that contained B in a concentration gradient of 0.000, 0.125, 0.250, 0.750, 5.000, 10.000, 20.000, and 40.000 mmol L−1 were conducted to investigate tobacco cultivar K326′s agronomic traits, photosynthetic performance, antioxidant enzymes, and boron and nicotine concentration. As B concentration increased, indices including leaves biomass and net photosynthetic rate (Pn) generally increased first and then decreased, which was in contrast to antioxidant enzymes, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT). With increasing B concentration, boron content in tobacco seedlings increased significantly by 24.00~96.44%, while decreased nicotine content by 21.60~82.03%. The highest biomass and photosynthetic performance were obtained within 0.75 and 5.00 mmol L−1 treatments. The results of the sandy soil pot verification experiment were similar to the hydroponic experiment obtained. The beneficial mechanism of moderate B on tobacco seedlings is to maintain cell structure integrity, enhance photosynthetic capability, and promote root growth. Consequently, the optimum B concentration for tobacco seedlings is 0.75~5.00 mmol L−1, and applying 0.25~0.50 B kg hm−1 in soil under available B insufficiency could meet the needs of the growth of flue-cured tobacco.